Impact of conventional urea and nano-urea with herbicide mixtures on wheat growth, weed suppression and nitrogen use efficiency - Sarkar, A; Singh, T; Parihar, C M; Das, T K; Mandal, A; Patra, K; Reddy, K S; Sinha, A; Sadhukhan, R; Dutta, A (Plant Science Today, 2026)
Conventional urea-based nitrogen management is often inefficient and promotes initial weed proliferation, yet the potential of nano urea to overcome these limitations under integrated weed management remains insufficiently explored. Therefore, the study hypothesises that integrating foliar-applied nano urea with reduced basal dose of conventional urea and herbicide mixtures may improve nitrogen allocation in favour of wheat rather than weeds, thereby enhancing productivity and nitrogen use efficiency compared to conventional urea-based management. Considering this, an experiment was undertaken during 2021–2022 at ICAR-Indian Agricultural Research Institute , New Delhi, using a split-plot design (SPD) on the impact of nano urea-based nitrogen management and new herbicide mixtures on wheat growth, productivity, profitability and nitrogen use efficiency. Four nitrogen management options in the main plots were tested: control (no nitrogen), 100 % recommended dose of nitrogen (RDN), 50 % RDN + 2 nano urea sprays (40 and 60 days after sowing – DAS) and 75 % RDN + 1 nano urea spray (60 DAS). Simultaneously, 4 weed management treatments in subplots included ready mix and tank mix herbicides, weed-free and un-weeded checks. Results revealed that 100 % RDN treatment significantly outperformed nano urea-based treatments in weed suppression, crop growth, profitability and nitrogen use efficiency, with achieving over 30 % higher productivity compared to 50 % RDN + 2 nano urea sprays along with herbicide mixtures. Various nitrogen use efficiency indicators showed that agronomic efficiency and apparent recovery efficiency both were highest in 100 % RDN through conventional urea-based treatment compared to nano urea-based treatments. However, partial factor productivity and partial nutrient balance were higher in nano urea-based treatments over conventional urea-based treatment.